(untitled) (Journal of Partial Differential Equations, 2021)
"The purpose of this paper is to establish an averaging principle for stochastic fractional partial differential equation of order 03b1 > 1 driven by a fractional noise. We prove the existence and uniqueness of the global mild solution for the considered equation by the fixed point principle. The solutions for SPDEs with fractional noises can be approximated by the solution for the averaged stochastic systems in the sense of p-moment under some suitable assumptions."